Civil Society and Disarmament 2016 - Bureau des affaires du désarmement des Nations Unies (United Nations, 2017)
The nascent movement to enact a nuclear ban treaty has reframed the problem of nuclear weapons from defense strategies to the issues of humanitarian and environmental consequences. This volume of Civil Society Engagement in Disarmament Processes presents a case for the nuclear ban treaty as a vital first step in nuclear weapons’ ultimate abolition.